Brexit and private international law, between Rome, Brussels and Lugano: “How can i just let you walk away?” - Cortese, Bernardo (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
What challenges does Brexit pose for private international law in civil and comercial matters, in EU/UK cases? How to address those challenges? The article attempts to answer these questions, with reference to the Rome I, Rome II, Brussels I(bis) Regulations and the 2007 Lugano Convention. In this context, the rules and legal principles applicable both during the transition period and afterwards are analysed. In particular, the prospects of a cliff-edge scenario at the end of the transition period are considered; jurisdiction and recognition of decisions are identified as areas in which legal traffic risks being heavily compromised. The article puts forward some proposals for a negotiating path capable of depotentiating that risk.
Keywords: private international law; jurisdiction; recognition of judgments; Brexit